INDEPENDENT INTEGRATED E-TRAINING ENVIRONMENT - Yasin, Asmaa; Ahmed, Bana; Hadary, Reem El; Jazyah, Yahia Hasan (International Journal of Engineering Technologies and Management Research, 2018)
Several programming contests are being held every year searching for the best team in programming. To achieve the first place in the context, training is a crucial factor for participants; where meeting regularly and face to face is important issue. In some cases, meeting face to face is not available for competent, so this research develops an algorithm for training and examining the source code of user. The algorithm is based on designing an additional thread to monitor and control the process of testing the source code. The algorithm is efficient and achieves high percentage of success.